Long-Term Motor Cortical Electrical Stimulation Ameliorates 6-Hydroxydopamine-Induced Motor Dysfunctions and Exerts Neuroprotective Effects in a Rat Model of Parkinson’s Disease - Kuo, Chi-Wei; Chang, Ming-Yuan; Chou, Ming-Yi; Pan, Chien-Yuan; Peng, Chih-Wei; Tseng, Hui-Chiun; Jen, Tsu-Yi; He, Xiao-Kuo; Liu, Hui-Hua; Nguyen, Thi Xuan Dieu; Chang, Pi-Kai; Hsieh, Tsung-Hsun (Frontiers in Aging Neuroscience, 2022)
Objective Cortical electrical stimulation (CES) can modulate cortical excitability through a plasticity-like mechanism and is considered to have therapeutic potentials in Parkinson’s disease (PD). However, the precise therapeutic value of such approach for PD remains unclear. Accordingly, we adopted a PD rat model to determine the therapeutic effects of CES. The current study was thus designed to identify the therapeutic potential of CES in PD rats. Methods A hemiparkinsonian rat model, in which lesions were induced using unilateral injection of 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle, was applied to identify the therapeutic effects of long-term (4-week) CES with intermittent theta-burst stimulation (iTBS) protocol (starting 24 h after PD lesion observation, 1 session/day, 5 days/week) on motor function and neuroprotection. After the CES intervention, detailed functional behavioral tests including gait analysis, akinesia, open-field locomotor activity, apomorphine-induced rotation as well as degeneration level of dopaminergic neurons were performed weekly up to postlesion week 4. Results After the CES treatment, we found that the 4-week CES intervention ameliorated the motor deficits in gait pattern, akinesia, locomotor activity, and apomorphine-induced rotation. Immunohistochemistry and tyrosine hydroxylase staining analysis demonstrated that the number of dopamine neurons was significantly greater in the CES intervention group than in the sham treatment group. Conclusion This study suggests that early and long-term CES intervention could reduce the aggravation of motor dysfunction and exert neuroprotective effects in a rat model of PD. Further, this preclinical model of CES may increase the scope for the potential use of CES and serve as a link between animal and PD human studies to further identify the therapeutic mechanism of CES for PD or other neurological disorders.